The Crime Of Money Laundering With The Origin Criminal Action Of Drug Trafficking In Supreme Court Decision No. 1303 K / Pid. Sus / 2013 Juncto High Court Decision No. 700 / Pid / 2012 / Pt.Mdn Juncto Medan District Court Decision No.1234 / Pid.B / 2012 - Ferdy Syahputra (NOMOI Law Review, 2020)
Pencucian uang or in English is called money laundering is not only threatening the economic stability and integrity of the financial system, but also harm the joints of the life of society, nation, and state based on Pancasila and the Constitution of the Republic of Indonesia Year 1945 Money laundering is done is to disguise the proceeds of crime. In this case, will be appointed on the crime of narcotics and drugs. This research uses a normative juridical research with descriptive analysis. The type of data used is secondary data sourced from primary, secondary and tertiary legal materials. Secondary data were collected by library research techniques. Next, the data is analyzed using qualitative analysis methods. Mode of crime in the banking sector, in this case, use money transfer services Money Changer (money changers). Predicate crime (crimes origin) it is a criminal offense drug, namely methamphetamine. Methamphetamine trade is carried out between cross country, namely between Malaysia and Indonesia.Keywords : Money, Laundering, Predicate, Crime, Narcotics.